Designing of metallic nanocrystals embedded in non-stoichiometric perovskite nanomaterial and its surface-electronic characteristics - Jagadeesh Suriyaprakash (Nature Portfolio, 2017)
Abstract Engineering of novel functional nanocomposite as like as the metallic nanocrystals supported non-stoichiometric perovskite nanomaterial in controlled parameters (size, shape and ratio of chemical characteristics) is a challengeable task. In this context, we present a facile route to fabricate and study its physicochemical property at real time mode in this report. Nanoscale pure Pb crystals surfaced on non-stoichiometric A-site deficient Pb1-xTiO3-y nanoparticle were fabricated when a precursor lead titanate (PbTiO3) nanoparticle was exposed to an electron beam irradiation (EBI) in a transmission electron microscope (TEM) at ambient temperature. In the state of the art, the chemical states and electronic structure of non-irradiated and irradiated PbTiO3 were studied by X-ray photoelectron spectroscopy (XPS). Electron bombardment resulted in a new visible feature at low binding energy in the Pb 4f core level, while Ti 2p and O 1s line shape showed slight changes. The Fermi level of the corresponding materials was determined to be 1.65 ± 0.1 eV and 2.05 ± 0.1 eV above the valence band maximum, respectively. The normal, weakly p-type PTO exhibits peculiar n-type feature after EBI process (The Fermi level moves near to the conduction band). A feasible mechanism is proposed involving the electron-stimulated local bond-breaking phenomenon in PbTiO3.